Pancasila Sebagai Ideologi Bangsa: Perwujudan Nilai Budaya dan Konsensus Dalam Keberagaman Indonesia - Ahmad Muhamad Musain Nasoha; Ashfiya Nur Atqiya; Desy Indah Pratiwi; Rachmanda Putri; Sabil An Naim (Majelis: Jurnal Hukum Indonesia, 2024)
Pancasila, as the ideology of the Indonesian nation, plays a crucial role in guiding both individual and collective life. As a worldview rooted in the nation's cultural values, Pancasila reflects local wisdom, acknowledged for its truth, and serves as a foundation for maintaining consistency in thought and action amidst Indonesia's plural society. This article employs a qualitative research method with philosophical and sociological approaches, utilizing literature reviews and critical analysis of various sources related to ideology and national values. The findings reveal that Pancasila possesses unique characteristics distinguishing it from other ideologies, particularly its ability to accommodate diversity without disregarding universal values. All principles of Pancasila are proven to be logical, relevant, and applicable in addressing social, political, and economic challenges, thereby reinforcing its role as an ideal guide for the Indonesian people. These findings affirm Pancasila’s distinctiveness as a unifying ideology adaptable to the dynamics of the times.